Comparative Analysis of Students’ Perception on Peer Editing Technique in Writing - Ersa Anita Aulia (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
The aim of the study is to analyze the students’ perception on Peer Editing Technique of grade ten students of MA Sultan Fattah Jepara and USANT. The method used in this study was descriptive qualitative research. The statistical tools used were the Weighted Mean and The Wilcoxon Rank. The following findings have surfaced: first, the responses of MA Sultan Fattah Jepara computed average weighted mean is 4.83, sum rank is 124,5 and the responses of University of Saint Anthony computed average weighted mean is 4.70, sum rank is 89,5. Both the two sets of responses have similar verbal interpretation very effective. Second, there is no significant difference in the two sets of responses and the use of Peer Editing Technique has positive effects in the both sets of students. Third, a peer editing module can be designed based from the findings of the study.